A Retrospective Survey of Buprenorphine Substitute Treatment With Minimal Dosage in Heroin Use Disorder - Shen, Wenwen; Wang, Qing; Zhang, Jianbin; Ping, Wenkai; Zhang, Jiawen; Ye, Weiting; Hu, Qianyu; Cerci, Deniz; Zhou, Wenhua (Frontiers in Psychiatry, 2019)
Objectives: It is widely accepted that buprenorphine maintenance treatment (BMT) with dosages above 8 mg daily is effective for patients with heroin use disorder. In this study, the authors evaluated the effectiveness of long-term BMT for heroin users in China, with dosages kept on a much smaller level. Methods: This is a retrospective observational study of seventy-two patients who had undergone detoxification and continued with buprenorphine maintenance between 2007 and 2016. Measurements such as self-reported relapse status, buprenorphine doses, protracted symptoms, general health condition, and self-reported side effects were included. Results: At the time of interview, 51 patients had remained abstinent at follow-up (including 13 who were opioid free). The dosages of buprenorphine were 1.33±0.88 (ranging 0.3-3.5) mg/day when maintenance treatment was initiated, and 1.2±0.8 (ranging 0.2-3.2) mg/day at the last follow-up. The remaining patients had either relapsed on heroin (n=11), or had switched to compulsory treatment (n=10). In general, abstinent patients had minimal protracted symptoms, especially in physical symptoms. Opioid free abstainers were more likely to report good physical health than patients on buprenorphine. Predictors of worse outcomes (relapsed or switched to compulsory treatment) were lower education levels, younger age, and younger onset of illicit drug use. Conclusions: This study shows promising results of minimal dosage BMT in treating heroin use disorder. We recommend further studies applying minimal dosage BMT in China and world-wide.